A cellulose-based chiral fluorescent sensor for aromatic nitro compounds with central, axial and planar chirality. Issue 14 (24th March 2017) - Ikai, Tomoyuki; Suzuki, Daisuke; Shinohara, Ken-ichi; Maeda, Katsuhiro; Kanoh, Shigeyoshi
Abstract : This is the first example of a powerful chiral fluorescent sensor applicable to a wide range of chiral compounds with central, axial and planar chirality. Abstract : Chiral sensing using fluorescent responses as output signals is an attractive technique for enantiodifferentiation in terms of its rapidity, high sensitivity, simplicity and high-throughput ability. However, because the reported sensors can only be applied to a limited type of chiral molecule (mainly compounds with a chiral center), it is still a great challenge to develop a powerful fluorescent sensor applicable to various types of chirality. Herein, we synthesized a novel chiral fluorescent sensor (Ce-3 ) containing a benzo[1, 2- b :4, 5- b ′]dithiophene-based π-conjugated group as a fluorescent signaling unit through a two-step polymer reaction, including carbamoylation and cross-coupling reactions, using microcrystalline cellulose as a starting material. The enantioselective fluorescence response of this modified cellulose to aromatic nitro compounds was investigated in solution and in the solid state. Ce-3 exhibited enantioselective fluorescence quenching for a wide range of aromatic nitro compounds with central, axial and planar chirality. Visual chiral detection based on a change of the visible emission color was also achieved with Ce-3 in conjunction with anthracene as an achiral fluorescent dye. A corresponding model molecule did not show any marked sensing ability, suggesting that the regular higher-order structure of Ce-3 plays a key role in this efficient chiral sensing.